'Quit and Stay Quit Monday' as a Novel Approach to Smoking Cessation: A Pilot Experimental Study. (7th August 2017) - De Leon, Elaine; Crossnohere, Norah L.; Fuentes, Laura W.; Johnson, Morgan; Welding, Kevin; Cohen, Joanna E.
Abstract : Introduction: Emerging evidence suggests a heightened interest in healthy behaviour changes, including smoking cessation, at the beginning of the week. Evidence from Google searches, quitlines, and cessation websites show greater information-seeking and interest in early week quitting. Aims: This pilot assesses the comparative effectiveness of a smoking cessation intervention that encourages participants to use Mondays as a day to quit or recommit to quitting smoking. Methods: We partnered with existing smoking cessation group programs to conduct a quasi-experimental, pre–post study. Both comparison and intervention groups received the same standard-care curriculum from program instructors. Intervention group participants received Monday materials including a wallet card and a mantra card during enrolment. On Mondays, intervention participants received an emailed tip-of-the-week and were encouraged to quit or recommit to quitting. Quit buddies were recommended in both groups, but intervention participants were encouraged to check-in with quit buddies on Mondays. The outcomes of smoking abstinence, number and length of quit attempts, and self-efficacy were assessed at the final program session and three months later. Results: At the last session, intervention group participants who were still smoking had a higher self-efficacy of quitting in the future, rated their programs as more helpful in quitting smoking, and were more likely to rate quit buddies as very helpful. Differences in self-efficacy were no longer observed at the second follow-up. No differences were observed between intervention and standard group participants in abstinence, number of quits, length of quits, or self-efficacy of staying quit at either follow-up. Conclusions: Encouraging results from this pilot study indicate that further research is needed to explore how Monday messaging may improve smoking cessation programs.